AN ANALYSIS OF WORD OF MOUTH MARKETING IN BUILDING CORPORATE REPUTATION: A CASE STUDY OF ADIPUTRA GUESTHOUSE - Shaynaqu Asmi Putri; Anas Hidayat (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the role of Word of Mouth (WoM) strategy in building corporate reputation, specifically at Adiputra Guesthouse as a hospitality service provider in Yogyakarta. Using a descriptive quantitative approach, data were collected through questionnaires distributed to 103 respondents who had used the guesthouse services. The study also applied the SERVQUAL model as a supporting variable to assess service quality in relation to customer perceptions of corporate reputation. The analysis reveals that the WoM strategy has a positive influence on the formation of Adiputra Guesthouse’s reputation, with good service quality reinforcing customers’ tendency to recommend the service. The dimensions of reliability and tangibles received the highest scores in service quality evaluation, while empathy and assurance require further improvement. These findings highlight the importance of actively managing WoM strategies and enhancing service quality to foster positive perceptions and strengthen the company’s reputation.